Study on Estimates of Travel Distance, Velocity and Potential Volume of Amahusu Sliding Plane using Energy Conservation Approach in Conjunction with Geoelectric Survey - Matheus Souisa; Lilik Hendrajaya; Gunawan Handayani (Journal of Mathematical and Fundamental Sciences, 2018)
The investigation of landslides applying various methods has been receiving increased attention in recent years. This study was aimed at assessing the estimated distribution of landslide movement using an energy conservation formula in a lumped mass model to obtain velocity and travel distance estimations, in combination with an inverted resistivity model for estimating the Amahusu landslide volume. The research location was in the Amahusu hills of the Nusaniwe subdistrict, Ambon, Indonesia. A survey was carried out using GPS and a geoelectric resistivity method with the Wenner-Schlumberger configuration. The results of the study provide a characterization of this rotational type landslide. The estimated landslide volume was 70,954 m3 and the estimated potential landslide volumewas 50,603 m3. This mass moved 303 m away from the original location, with an estimated maximum velocity of up to 21.25 m/s. The displacement pattern of a landslide mass is primarily controlled by the geometry of the sliding plane. The geometry of the sliding plane causes different types of movement, based on which the possible occurrence of a future landslide can be predicted.